2023
DOI: 10.1111/sji.13263
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic NKT cells attenuate urogenital chlamydial clearance and enhance infertility

Abstract: Urogenital chlamydial infections continue to increase with over 127 million people affected annually, causing significant economic and public health pressures. While the role of traditional MHCI and II peptide presentation is well defined in chlamydial infections, the role of lipid antigens in immunity remains unclear. Natural killer (NK) T cells are important effector cells that recognize and respond to lipid antigens during infections. Chlamydial infection of antigen‐presenting cells facilitates presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In contrast, there is no significant difference in the severity or incidence of tubal effusion in Jα18-/-(iNKT-deficient) mice compared with WT controls. Thus, non-invariant NKT cells have an immunopathogenic role in urogenital tract chlamydial infection ( 95 ). This partly explains a seemingly contradictory earlier study that NK T cells triggered pathological Th2 responses during chlamydial infection ( 96 ).…”
Section: Evasion Of Innate-like Lymphocytes [Ills]mentioning
confidence: 99%
“…In contrast, there is no significant difference in the severity or incidence of tubal effusion in Jα18-/-(iNKT-deficient) mice compared with WT controls. Thus, non-invariant NKT cells have an immunopathogenic role in urogenital tract chlamydial infection ( 95 ). This partly explains a seemingly contradictory earlier study that NK T cells triggered pathological Th2 responses during chlamydial infection ( 96 ).…”
Section: Evasion Of Innate-like Lymphocytes [Ills]mentioning
confidence: 99%
“…Natural killer T (iNKT) cells represent a subset of innate lymphocytes that possess the characteristics of NK and αβ T cells. iNKT cells play an essential role in the early stages of immune responses and can also produce cytokines that regulate subsequent adaptive immune responses against infectious pathogens [26,27]. Our previous work examined the interactions of iNKT/NK and iNKT/DC after Chlamydia lung infection and found that iNKT is a critical regulator in innate and adaptive immune responses [28][29][30].…”
Section: Introductionmentioning
confidence: 99%